142 Prenatal Sleep Quality and Infant Sleep: A Longitudinal Study. (3rd May 2021) - Burdayron, Rebecca; Pennestri, Marie-Helene; Keys, Elizabeth; Tomfohr-Madsen, Lianne; Giesbrecht, Gerald
Abstract: Introduction: Poor sleep quality is common during pregnancy and can increase the risk of adverse obstetric and fetal outcomes. Existing research on the association between prenatal sleep and infant sleep is scarce and has focused on other aspects of prenatal sleep such as sleep duration, chronotype, and insomnia symptoms. To our knowledge, no studies have examined the association between prenatal sleep quality and infant sleep outcomes. Thus, this study aimed to investigate whether maternal sleep quality during pregnancy was prospectively associated with infant sleep dimensions, independent of relevant covariates. Methods: Participants were a subset of 272 mother-infant dyads enrolled in an ongoing cohort study. Maternal prenatal sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI) in early to mid- (M gestational age = 15.12 ± 3.56 weeks) and late- (M gestational age = 32.44 ± 0.99 weeks) pregnancy. Mothers completed the Brief Infant Sleep Questionnaire (BISQ) at 3, 6, and 12 months postpartum. The following infant sleep parameters were assessed: sleep duration (day, night, 24-hour), number of night awakenings, and wake after sleep onset. Prenatal depressive symptoms were assessed with the Edinburgh Postnatal Depression Scale (EPDS) at both pregnancy time points. Other covariates included maternal age at enrollment, infant age, parity, and co-sleeping status. Results: Generalized estimating equations (GEE) models revealed that poorer maternal sleep quality during early-to-mid pregnancy did not significantly predict infant sleep parameters after adjustment for covariates (p > .05). However, in late pregnancy, poorer maternal sleep quality significantly predicted shorter 24-hour sleep duration and longer wake after sleep onset, but not daytime sleep duration, nighttime sleep duration, and number of night awakenings (p < .05). Conclusion: Study findings advance our understanding of the prospective link between maternal prenatal sleep quality and infant sleep. Results indicate that maternal sleep quality during late gestation may play a role in the development of infant sleep patterns. These findings have important implications for intervention efforts targeting maternal sleep quality during pregnancy. Future research should use objective measures of sleep, such as actigraphy, to better elucidate the effects of prenatal sleep quality on infant sleep outcomes. Support (if any): The Canadian Institutes of Health Research (CIHR)